Genetic-enviroment interactions in tropical beef cattle - Maltos, Joel; Alba, Jorge de (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Two trials were conducted with progeny of Brahman bulls, Sta Gertrudis and Romo Sinnano, to determine genetic-environment interactions that could interfere with selection based on progeny tests for post-weaning weight gains. In the first trial, the same calves were first subjected to a diamond paddock environment 100 days post-weaning and immediately thereafter to a stud environment. Changes were observed in the order of merit of the bulls' progenies. One bull, Sta Gertrudis, ranked last in the paddock and first in the stud. This change is attributable to a negative correlation between weaning weight and post-weaning performance in the Sta Gertrudis bull